Online Teaching Management and Supporting Factors Under The Pandemic Situation COVID-19 with The Online Meeting Platform - Wongsawad, Thutsapong; Kiddee, Atipong; Kenikasahmanworakhun, Phatthararuethai; Pleangsorn, Pornrapat (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2022)
The objectives of this research were to study: 1. the online teaching and learning management and supporting factors under the pandemic situation COVID-19 with online meeting platforms; 2. Compare the differences of online teaching and learning management of personal and supporting factors and 3. to find the relationship between online teaching and learning management of personal and supporting factors, the respondents used in the research were undergraduate students in year 1-4 of the academic year 2020 as group sampling from 206 people, the research instrument was questionnaire, the statistics used for data analysis were mean and standard deviation, the statistics used in the test was t-test, F-test by one-way analysis of variance and Pearson's correlation coefficient. The results showed that online teaching management an overview at high level, the results of comparing the differences in teaching and learning management found that personal and supporting factors were significantly different at .05; there was high level of positive correlation and same direction statistically significant at .05